2017
DOI: 10.3892/ol.2017.5577
|View full text |Cite
|
Sign up to set email alerts
|

Six1 expression is associated with a poor prognosis in patients with glioma

Abstract: Abstract. Glioma is the most common human brain cancer and has poor prognosis. Messenger RNA profiling identified that sineoculis homeobox homolog 1 (Six1) is dysregulated in glioma tumor progenitor cells from glial progenitor cells isolated from normal white matter. However, the expression and role of Six1 in glioma remains unclear. The purpose of the present study was to investigate the expression level of Six1 in glioma tissues and the association between Six1 expression and clinicopathological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Similarly, Lerbs, et al20 indicated that SIX1 could be a stem cell marker and promote cell metastasis in pancreatic cancer. Additionally, SIX1 was deemed a prognostic factor predictive of poor prognosis in glioma 21. In the present study, we found miR-362 to be downregulated in CRC tissues and cell lines, and discovered that low expression of miR-362 predicted poor overall survival in CRC patients.…”
Section: Introductionsupporting
confidence: 58%
“…Similarly, Lerbs, et al20 indicated that SIX1 could be a stem cell marker and promote cell metastasis in pancreatic cancer. Additionally, SIX1 was deemed a prognostic factor predictive of poor prognosis in glioma 21. In the present study, we found miR-362 to be downregulated in CRC tissues and cell lines, and discovered that low expression of miR-362 predicted poor overall survival in CRC patients.…”
Section: Introductionsupporting
confidence: 58%
“…Concerning ANGPT2 , the methylation status of 6 CpGs near the gene transcription site (four of which were analyzed in this study) has already been shown to predict overall survival of chronic lymphocytic leukemia patients (Martinelli et al ., ). Several studies have reported that SIX1 overexpression is frequently associated with poor patient prognosis in various malignancies, as colorectal cancer (Kahlert et al ., ) and glioma (Zhang and Xu, ), however not in melanoma. Besides, the mechanisms responsible for the high expression of SIX1 have been poorly investigated.…”
Section: Discussionmentioning
confidence: 98%
“…[23][24][25] In our concurrent study, in cultured melanoma cells, SIX1 was proven to promote cell proliferation and invasion, and SIX1 expression could be inhibited by miR-150-5p, which exhibited inhibitory functions in melanoma cell. 26 However, the in vivo metastatic functions and the clinical significance of SIX1 in melanoma are unknown. Thus, underlying the mechanisms of SIX1 regulation in melanoma and the upstream factors of SIX1 would be conducive to clinical treatments.…”
Section: Discussionmentioning
confidence: 99%